Intervenciones sostenibles a escala de manzana para el centro histórico de Santiago de Cali. - Arévalo Jiménez, Jordy; García Álvarez, Jhon Alexander (Universidad Antonio Nariño, 2022)
This degree project is born from the importance that its urban historical centrality or "historical center" has for cities, mainly due to the heterogeneity of uses, the ethnic multiculturalism that daily converge in the sector and its important historical connotation that its urban spaces and architectural artifacts have had for the citizen and the collective memory.